The Influence Of Social Network And Self Efficacy On Job Attainment: The Role Of Work Readiness Mediation - Nindya Putri Maharani; Kussudyarsana Kussudyarsana (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study investigates the influence of social networks and self-efficacy on university graduates’ job attainment, with work readiness as a mediating factor. Employing a quantitative survey method, data were collected from 200 purposively sampled 2024–2025 graduates domiciled in Central Java using structured online questionnaires. Social networks refer to formal and informal connections for accessing information, support, and job opportunities, while self-efficacy reflects individuals’ confidence and resilience in planning and executing career-related actions. Work readiness encompasses skills, knowledge, and personal attributes enhancing employability, and job attainment measures post-graduation employment success in terms of speed, relevance, and quality. The analytical strategy adopted a Partial Least Squares method via SmartPLS 4.0 to test the proposed model. Measurement properties were first confirmed through validity and reliability checks, followed by structural testing to determine the presence of direct, indirect, and mediating effects. The results show that social networks and self-efficacy significantly influence job attainment, both directly and indirectly through work readiness, highlighting the importance of external support, internal belief, and competency development in securing employment. The study also notes limitations related to sample scope and respondent subjectivity.